Interactive Dance Learning : Enhancing High School Students’ Critical Thinking Skills - Stefi Winda Pratiwi; Elindra Yetti; Rizky Taufik Rakhman (International Journal of Educational Development, 2025)
This study investigates the effect of interactive learning in traditional dance education on students’ critical thinking skills at the senior high school level. The background highlights the dominance of rote-based teaching in dance classes and the lack of reflective and analytical approaches that can foster students’ higher-order thinking. A quasi-experimental method with a pretest-posttest control group design was employed, involving 72 tenth-grade students from several high schools in South Jakarta. The experimental group received interactive dance instruction integrating reflection, interpretation, and peer discussion, while the control group received conventional instruction. Data were collected through critical thinking tests, classroom observations, and student perception questionnaires. The results showed a significant improvement in the experimental group’s critical thinking scores, with a posttest average of 88.2 and a gain score of 0.71 (high category), compared to the control group’s posttest average of 66.7 and gain score of 0.21 (low category). Paired t-test and independent t-test analyses confirmed statistically significant differences (p < 0.05) between the two groups. Observation and questionnaire data revealed that students in the interactive group exhibited higher engagement in critical thinking activities such as interpretation, evaluation, and reasoning. These findings confirm that interactive dance learning not only enhances aesthetic understanding but also promotes critical thinking, making it a valuable pedagogical approach for 21st-century education.